The Legends of Elendor: Educational Gamification as an Influential Factor in Academic Flow and Academic Performance in Socially Depressed Communities - Ana Manzano-León; José M. Rodríguez-Ferrer; José M. Aguilar-Parra; Carlos Salavera (Education Sciences, 2022)
Secondary education needs to find learning strategies that favor student engagement, particularly in socially deprived communities. The objective of this study is to analyze the influence of gamification on educational flow and academic performance. A quasi-experimental pre-test/post-test study has been carried out with 207 secondary school students that compares the gamified cooperative learning method with the directive teaching methodology. The results show statistically significant differences in perceived class flow and academic performance in favor of the gamified group. In addition, it has been analyzed whether these improvements vary according to sex, proving that the gamified methodology is just as effective for girls as for boys. It is concluded that the game systems achieved with gamification favor student engagement because they perceive the tasks as enjoyable and immersive.